The extent of including logical intelligence in the Book of chemistry for the fifth Grade of science (Journal Of Educational and Psychological Researches, 2022)
The aim of the current research to determine the extent of logical intelligence in the book of chemistry for the fifth grade of science and to achieve the goal the researcher has prepared a special criterion in the areas of logical intelligence main and sub-to be included in the book after reviewing the previous literature and studies in this regard may be the final form after presentation to experts and arbitrators in the field of Educational and psychological sciences, curricula and teaching methods from (3) main areas and (21) sub-fields, then the researcher analyzed the book Bibih and applied branches and adopted the idea of ​​both explicit and implicit as a unit of registration and repetition as a unit of the census, The results showed that the book included (290) repetitions as the biological branch ranked first with (160) repetition rate (55.17%), and the second branch applied (130) repetition rate (44.83%). Based on the results, the researcher recommended the need to include the book for the main and sub-logical intelligence areas in an integrated and balanced manner according to scientific developments, and suggested several proposals, including a study to know the impact of logical intelligence on the achievement of preparatory stageStudents in chemistry and their ability to solve problems, note that the statisticalMethods that Adopted is the Holste equation and percentage.